Pengaruh hereditas dan lingkungan dalam proses pendidikan - Zahra, Ghefira Az (Maliki Interdisciplinary Journal, 2025)
This study discusses the influence of heredity and environment on individual development in the educational process. Heredity includes genetic factors inherited from parents, such as intelligence, talents, and physical traits, while the environment encompasses social and physical aspects that affect a child's development. These two factors work together to shape a student's characteristics and abilities. The interaction between heredity and environment determines an individual's development outcomes, where genetic potential must be supported by a conducive environment to achieve optimal educational results. Therefore, the roles of family and school are crucial in creating an environment that supports the child's learning development. Heredity and environment are two interrelated factors that influence a person's development during the educational process. Heredity provides innate traits, such as intelligence and talent, but it is the environment that helps develop these abilities.